The ITS1-5.8S-ITS2 Sequence Region in the Musaceae: Structure, Diversity and Use in Molecular Phylogeny - Hřibová, Eva (Public Library of Science, 2011)
Genes coding for 45S ribosomal RNA are organized in tandem arrays of up to several thousand copies and contain 18S, 5.8S and 26S rRNA units separated by internal transcribed spacers ITS1 and ITS2. While the rRNA units are evolutionary conserved, ITS show high level of interspecific divergence and have been used frequently in genetic diversity and phylogenetic studies. In this work we report on the structure and diversity of the ITS region in 87 representatives of the family Musaceae. We provide the first detailed information on ITS sequence diversity in the genus Musa and describe the presence of more than one type of ITS sequence within individual species. Both Sanger sequencing of amplified ITS regions and whole genome 454 sequencing lead to similar phylogenetic inferences. We show that it is necessary to identify putative pseudogenic ITS sequences, which may have negative effect on phylogenetic reconstruction at lower taxonomic levels. Phylogenetic reconstruction based on ITS sequence showed that the genus Musa is divided into two distinct clades – Callimusa and Australimusa and Eumusa and Rhodochlamys. Most of the intraspecific banana hybrids analyzed contain conserved parental ITS sequences, indicating incomplete concerted evolution of rDNA loci. Independent evolution of parental rDNA in hybrids enables determination of genomic constitution of hybrids using ITS. The observation of only one type of ITS sequence in some of the presumed interspecific hybrid clones warrants further study to confirm their hybrid origin and to unravel processes leading to evolution of their genomes.